The medical war British military medicine in the First World War - Harrison, Mark, 1964- (Oxford University Press, 2010)
'The Medical War' describes the role of medicine in the British Army during the First World War. It argues that medicine played a vital part in the war, helping to sustain the morale of troops and their families, and reducing the wastage of manpower.